The information and support needs of patients living with inflammatory bowel disease: A qualitative study. (June 2022) - Karadag, Paige; Morris, Beth; Woolfall, Kerry
Objectives: To explore patients' experiences of living with inflammatory bowel disease (IBD) with a focus on their information and support needs. Methods: Qualitative interview study involving adults diagnosed with IBD recruited through social media. Interviews were audio recorded, transcribed and data were analysed thematically. Results: Interviews with 15 patients (9 females, 6 males) highlighted how misdiagnosis or hesitation to diagnose had caused frustration and anxiety. Once diagnosed, only a few participants received detailed information about IBD from their doctor. Negative experiences shared on social media caused initial anxiety, as individuals assumed that they may have a similar experience, yet online communities enabled insights into the experiences of others, helping patients adjust to living with IBD. Participants described both positive and negative impacts of living with IBD, including improved confidence and periods of anxiety. Discussion: Our findings highlight the importance of clear information and support from health professionals, as well as the benefits of online communities for ongoing support. At the point of diagnosis, patients would benefit from information about what IBD is, as well as how it may impact day to day life from doctors so that social media is not the only source of initial information about IBD.